PENGARUH METODE PEMBELAJARAN BAHASA ARAB KOMUNIKATIF (COMMUNICATIVE LANGUAGE TEACHING) TERHADAP KEMAHIRAN BERBAHASA PADA KELAS BAHASA (CELAD) MAHASISWA FAI-UIR - Yenni Yunita; Ismail Akzam; Pebrian, Rojja (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
The communicative method is a method that relies more on students’ creativity in doing exercises. At this stage, the direct roles of instructors/tutors are being reduced to provide opportunities for students to develop their own abilities. The students are emphasized to speak more than the instructors do. In the context of teaching Arabic at the Faculty of Islamic Studies of UIR, a language center institution called CELAD (Center For Languages and Academic Development) has been established as a means for teaching and developing foreign languages including Arabic which aims to make students understand Arabic both speaking and writing and able to apply it. The method used in this study is a quantitative method. In this study, the population consists of 327 students from four study programs of PAI, EKISY, PIAUD, PBS at FAI UIR. While the sample consists of 100 students. The conclusion of this study shows that: There is a a significant influence of Communicative Language Teaching Method on students’ Arabic proficiency in Language Classes (CELAD) of FAI-UIR.